Pegylated calixarene compound as well as preparation method and application thereof
By developing pegylated cup aromatic compound (DAC4A), azo reductase in the hypoxic environment is used to break the azo bond and the absorption of nitric oxide is achieved, solving various problems existing in existing drugs for treating inflammatory diseases, and achieving efficient and safe anti-inflammatory treatment effects.
Patent Information
- Application Number
- CN202510076363.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The existing drugs for treating inflammatory diseases have problems such as long treatment cycles, poor water solubility, gastrointestinal irritation and side effects of osteoporosis, and the nitric oxide absorption system is relatively single, making it difficult to achieve the expected therapeutic effect.
A polyethylene glycolized cup aromatic compound (DAC4A) was developed to achieve the absorption of nitric oxide by breaking azo bonds using overexpressed azo reductase in an oxygen-depleted microenvironment, releasing ortho-phenylenediamines capable of reacting with nitric oxide. This compound can collaborate with curcumin to prepare anti-inflammatory drugs, using nano micelle structures to achieve precise loading and release of drugs.
It has achieved efficient absorption of excess nitric oxide in an oxygen-deficient environment, reduced inflammation, and synergistically enhanced the therapeutic effect of anti-inflammatory drugs, and has good biocompatibility and stability.
Smart Images

Figure CN119875106A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polyethylene glycol calixarene compound, and also relates to a preparation method and application of the compound. Background Art
[0002] Nitric oxide (NO) is a member of the endogenous signaling molecules, involved in physiological pathways such as immune response, vasodilation and cell apoptosis. NO plays different roles in the body depending on concentration and exposure time; low concentrations can promote cell proliferation and play an anti-inflammatory role; but high concentrations can easily cause cell apoptosis and play a pro-inflammatory role. Excessive nitric oxide can induce the production of inflammatory factors, leading to synovial inflammation and cell apoptosis. At the same time, excessive NO induces strong nitrosative stress (RNS), recruits immune cells, and increases the number of osteoclasts, causing cartilage damage; compared with the unexpected side effects caused by direct inhibition of nitric oxide synthase (iNOS), selective removal of excess NO is one of the effective strategies for treating inflammation.
[0003] As a third-generation macrocyclic carrier, calixarene has attracted extensive attention in recent years. Calixarene is a hollow ring structure synthesized from phenol and formaldehyde in the presence of strong acid or alkali. It is cup-shaped, and the size of the cavity can be determined by the number of benzene rings. It itself has poor solubility in water or organic matter, but there are various methods for modifying its structure. Among them, azocalixarene can be constructed by connecting azo bonds. It is often used as a low-oxygen-sensitive macrocyclic carrier and plays a role in drug delivery, gene therapy, environment and food. At the same time, its reduction product aminocalixarene has natural reactive oxygen scavenging ability and has important application value in the treatment of related inflammatory diseases.
[0004] Existing drugs for treating inflammatory diseases have side effects such as long treatment cycles, poor water solubility, gastrointestinal irritation, and osteoporosis, and the reported nitric oxide absorption system is relatively simple, making it difficult to achieve the expected therapeutic effect. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a pegylated calixarene compound for regulating nitric oxide absorption under hypoxic environment, and also to provide a preparation method of the above-mentioned pegylated calixarene compound and its application in the preparation of drugs for treating hypoxia-related inflammation.
[0006] Technical solution: The present invention discloses a polyethylene glycol calixarene compound, the structure of which is shown in Formula I:
[0007]
[0008] Here, n is an integer of 4 to 8, and m is an integer of 2 to 44.
[0009] The preparation method of the above-mentioned polyethylene glycol calixarene compound DAC4A comprises the following steps:
[0010] (1) Using 4-tert-butylcalixarene and phenol as raw materials, a calixarene is obtained by reverse Friedel-Crafts alkylation in a toluene solution containing aluminum chloride, thereby forming a macrocyclic molecular skeleton 1-1;
[0011] (2) Using 3,4-diaminobenzoic acid and 9-fluorenylmethyl-N-succinimidyl carbonate as raw materials, a single protection of the meta-amino group is achieved through a nucleophilic reaction to form intermediate 2-1;
[0012] (3) The macrocyclic molecular skeleton 1-1 and the intermediate 2-1 are subjected to diazotization reaction to obtain the intermediate 3-1;
[0013] (4) Using polyethylene glycol monomethyl ether and p-toluenesulfonyl chloride as raw materials, intermediate 4-1 was synthesized, and then stirred in aqueous ammonia to obtain intermediate 4-2;
[0014] (5) The intermediate 3-1 is deprotected under the action of 1,8-diazabicyclo[5.4.0]undec-7-ene, i.e., DBU, and the meta-amino group is protected by Boc, and then connected with the intermediate 4-2 by amidation reaction, and the Boc protection is removed to obtain the pegylated calixarene compound of the present invention.
[0015] Wherein, its synthetic route, step (1) is:
[0016]
[0017] Wherein, step (2) is:
[0018]
[0019] Wherein, step (3) is:
[0020]
[0021] Wherein, step (4) is:
[0022]
[0023] Wherein, step (5) is:
[0024]
[0025] The invention also discloses a PEGylated calixarene nano-micelle, which is prepared from a PEGylated calixarene compound, with the hydrophilic chain end facing outwards and exposed in the water phase, and the hydrophobic benzene ring skeleton facing inwards to form a core, forming a stable spherical structure of the nano-micelle containing multiple cavities on the surface.
[0026] The method for preparing the nano micelles comprises the following steps:
[0027] Weigh DACnA and the drug and place them in a glass bottle, fully dissolve them in the organic phase, and remove the solvent by evaporation under reduced pressure to obtain a uniform film; add the preheated aqueous phase, continue ultrasonication, and filter with a membrane to obtain nanomicelles.
[0028] Wherein, the drug is an anti-inflammatory drug, the organic phase is chloroform, the aqueous phase is PB buffer solution, and the organic phase: aqueous phase = 1:2-5 (v:v).
[0029] The ultrasonic time is 5-20 min and the filtration is carried out through a 0.45 μm filter membrane.
[0030] The above-mentioned PEGylated calixarene compound or PEGylated calixarene nano-micelle can be used to regulate nitric oxide absorption in an oxygen-deficient environment.
[0031] The PEGylated calixarene compound or PEGylated calixarene nano-micelle can also be used in the preparation of anti-inflammatory drugs.
[0032] The application is that PEGylated calixarene compounds or PEGylated calixarene nano-micelles and curcumin are used in synergistic preparation of anti-inflammatory drugs.
[0033] Principle of the invention: The present invention discloses a PEGylated calixarene compound DAC4A for regulating nitric oxide absorption under hypoxia. The PEGylated calixarene described in the present invention is the first to integrate nitric oxide absorption with calixarene drug-carrying molecules to construct a synergistic treatment platform. The PEGylated calixarene compound is formed by connecting a skeleton molecule with diaminobenzoic acid with meta-protection through a diazotization reaction, and then the hydrophilic polyethylene glycol molecule is modified by the free carboxyl group at the upper end to construct an amphiphilic molecule; the compound can be used as a carrier to achieve the cleavage of the azo bond under the action of overexpressed azoreductase in a hypoxic microenvironment, and the freed o-phenylenediamine structure can react with nitric oxide to achieve the effect of absorbing excess nitric oxide.
[0034] The compound can be prepared into nano-micelle assemblies by a thin film dispersion method, and the selected polyethylene glycol monomethyl ether is modified at the upper end of azocalix aromatics through an amidation reaction, which can provide sufficient hydrophilic segments, and together with the benzene ring skeleton at the lower edge, an amphiphilic macrocyclic molecule is constructed, thereby self-assembling to form nano-micelles. The nano-micelle is both a carrier and a therapeutic agent, and the post-processing is relatively simple. Anti-inflammatory drugs can also be loaded in the macrocyclic cavity through host-guest interaction for synergistic anti-inflammatory. The self-assembled nano-micelle based on macrocyclic amphiphilic reagents integrates multiple macrocyclic cavities into a single nanoparticle, and has the function of realizing drug hypoxia release and quantitative loading of multiple drugs, while relying on its own active oxygen scavenging and nitric oxide absorption to achieve the purpose of synergistic treatment. This delivery system is of great significance for expanding the new structure of macrocyclic carriers in anti-inflammatory aspects and developing synergistic therapies with new drugs and carriers to achieve spatiotemporal consistency.
[0035] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The PEGylated calixarene compound of the present invention has a precise molecular weight, and multiple macrocyclic cavities can be integrated into the same nanoparticle to achieve precise loading of multiple drugs; at the same time, the surface-modified polyethylene glycol hydrophilic segment has good biocompatibility and can prolong the circulation in the body; the macrocyclic molecule can be reduced by overexpressed azoreductase in a hypoxic microenvironment to achieve precise release of the drug and simultaneously induce the absorption effect of nitric oxide; (2) The synthesis method and post-treatment are simple and easy to operate. The micelle preparation adopts a thin film dispersion method, which is simple and easy to operate. The prepared micelle structure is stable and relatively uniform, and has good reproducibility; (3) When used in the preparation of anti-inflammatory drugs, the macrocyclic molecule can load curcumin molecules in the cavity under the interaction of host and guest, which is used to solve the shortcomings of relying solely on its own anti-inflammatory activity and achieve a synergistic effect in treating inflammation. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is the NMR characterization image of the intermediate compound 1-1 in Example 1;
[0037] Figure 2 This is the NMR characterization image of the intermediate compound 2-1 in Example 1;
[0038] Figure 3 This is the NMR characterization image of the intermediate compound 3-1 in Example 1;
[0039] Figure 4 This is the NMR characterization image of the intermediate compound 4-2 in Example 1;
[0040] Figure 5 This is the NMR characterization image of the intermediate compound 5-1 in Example 1;
[0041] Figure 6 This is the NMR characterization image of the target product DAC4A in Example 1;
[0042] Figure 7 It is a fitting curve diagram of the fluorescence titration curve and binding constant of DAC4A and curcumin in Example 2, wherein A is the direct fluorescence titration curve of DAC4A and RhB, B is the fitting curve of direct fluorescence titration, C is the competitive fluorescence titration curve of DAC4A and curcumin, and D is the fitting curve of competitive fluorescence titration;
[0043] Figure 8 The particle size distribution diagram of DAC4A nanomicelles before and after drug loading in Example 3, wherein A is after drug loading and B is before drug loading;
[0044] Fig. 9 is the Fourier transform infrared spectrum of DAC4A nanomicelles in Example 3;
[0045] Fig.10 is the in vitro drug release curve of DAC4A nanomicelles in Example 5;
[0046] Fig.11 This is a graph showing the particle size change of DAC4A nanomicelles in Example 6 under an in vivo simulated environment;
[0047] Fig.12 The UV spectrum after SDT treatment in Example 7 and the absorbance value at 365 nm (A) and time relationship curve (B);
[0048] Fig.13 The UV spectra of DAC4A under the change of NO concentration before and after SDT treatment in Example 8, wherein A is the initial UV spectra of the sample group after SDT treatment, B is the change of the absorption peak with the increase of NO concentration, and C is the control group;
[0049] Fig.14 The in vitro NO absorption was determined by the Griess reagent method in Example 8;
[0050] Fig.15 This is a schematic diagram of the cell survival rate of the toxicity test of DAC4A nanomicelles on RAW cells in Example 9;
[0051] Fig.16 This is the intracellular NO absorption fluorescence image of DAC4A in Example 10;
[0052] Fig.17 The effect of different molecular weight PEG modification on the hypoxia responsiveness of DAC4A in Example 11;
[0053] Fig.18 The effect of different molecular weight PEG modification on NO absorption of DAC4A in vitro in Example 11;
[0054] Fig.19The effect of different molecular weight PEG modification on DPPH free radical scavenging of DAC4A in vitro in Example 11. DETAILED DESCRIPTION
[0055] The technical scheme of the present invention is further described below in conjunction with the examples. The test materials used in the examples can all be purchased through conventional channels.
[0056] Example 1
[0057] The synthesis route of the pegylated calix[4]arene for regulating nitric oxide absorption under hypoxia is as follows:
[0058]
[0059]
[0060] Synthesis and structural characterization of intermediate compound 1-1:
[0061] 4-tert-Butylcalix[4]arene (4.4 g, 6.78 mmol) was dissolved in a reaction flask containing toluene (100 mL), phenol (4.5 g, 47.8 mmol) was weighed and slowly dripped into the flask, and toluene (10 mL) was added, and then aluminum chloride (8 g, 60 mmol) was added, and stirred at 60°C overnight. After cooling to room temperature, hydrochloric acid (3%, v / v, 100 mL) was added and stirred for 30 min, the aqueous phase was washed once with toluene, the organic phases were combined, dried over anhydrous sodium sulfate, filtered and the toluene was dried by spin drying, the semi-solid residue was slurried with methanol (35 mL), the precipitate was filtered and vacuum dried to obtain an off-white solid powder crude product, and then the crude product was dissolved in chloroform (10 mL) at 55°C, and the above crude product solution was added to methanol (50-80 mL) to precipitate a white solid powder (2.38 g, yield 82%), i.e., the intermediate compound 1-1.
[0062] 1 H NMR (400MHz, DMSO-d6) δ9.77 (s, 4H), 7.12 (d, J = 7.5Hz, 8H), 6.65 (t, J = 7.5Hz, 4H), 3.88 (s, 8H).
[0063] Synthesis and structural characterization of intermediate compound 2-1:
[0064] 3,4-diaminobenzoic acid (2g, 13.1mmol) was dissolved in 0.1M sodium bicarbonate solution: acetonitrile (1:1, v / v, 50mL) to obtain a brown slurry. 9-fluorenylmethyl-N-succinimidyl carbonate (4.4g, 13.1mmol) was added to the slurry in small batches within 5min, and stirred at room temperature for 16-18h. TLC monitoring (ethyl acetate: petroleum ether = 1:1) showed that the solution became lighter and clearer. The reaction mixture was acidified with 1M hydrochloric acid (15mL), and the solution turned brown. The precipitate was filtered and washed with cold water, cold ether, n-hexane and methanol in turn, and then vacuum dried to obtain a gray solid (4.65g, yield 95%), which was the intermediate compound 2-1.
[0065] 1 H NMR (400MHz, DMSO-d6) δ8.79 (s, 1H), 7.99-7.21 (m, 9H), 6.72 (d, J = 8.4Hz, 2H), 5.70 (s, 2H), 4.52-4.25 (m, 3H).
[0066] Synthesis and structural characterization of intermediate compound 3-1:
[0067] Calix[4]arene (0.4 g, 0.94 mmol) and sodium acetate (0.98 g, 12 mmol) were dissolved in methanol: N, N-dimethylformamide (5:8, v / v, 13 mL) to obtain solution A (PH 7-10). Intermediate 2-1 (1.58 g, 4.23 mmol) and hydrochloric acid (37%, v / v, 2 mL) were dissolved in N, N-dimethylformamide solution (24 mL), and then the solution was placed below -5°C, and sodium nitrite aqueous solution (5 mL, 6%, w / w) was slowly added dropwise to the above solution, and reacted at low temperature for 30 min to obtain solution B.
[0068] Solution B was slowly added dropwise to solution A at -5°C to obtain a suspension. After stirring at room temperature for 2-3 hours, the pH was adjusted to 1 with hydrochloric acid (37%, v / v, 15 mL). Stirring was continued for 30 minutes. The mixture was filtered, washed repeatedly with water and methanol, and dried to obtain a yellow powder (1.4 g, yield 75%), which was the intermediate compound 3-1.
[0069] 1H NMR (300MHz, DMSO-d6) δ8.50–8.44(m,4H),8.34(d,J=8.6Hz,4H),8.09(dd,J=8.6,1.5Hz,4H),7.89(dd,J=29.9,7 .5Hz,20H),7.50–7.30(m,20H),7.10(d,J=7.5Hz,8H),5.01(d,J=6.7Hz,8H),4.60(d,J=6.7Hz,4H),3.86(s,8H).
[0070] Synthesis and structural characterization of intermediate compound 4-2:
[0071] Dissolve polyethylene glycol monomethyl ether (MW = 1000, 15g, 15mmol) in a reaction flask containing dichloromethane (200mL), then add p-toluenesulfonyl chloride (7.15g, 37.5mmol) and potassium hydroxide (8.4g, 150mmol), seal with a balloon, and react at 28°C for 12h. Monitor by TLC (dichloromethane: methanol = 10:1). Wash the organic phase with 2M hydrochloric acid (100mL×2), take the lower organic phase, dry it with anhydrous sodium sulfate, filter and spin dry the organic phase to obtain a viscous liquid, then precipitate it with cold anhydrous ether, filter the precipitate and pump it dry with an oil pump to obtain a white powder (13.5g, yield 90%), which is the intermediate compound 4-1.
[0072] The intermediate 4-1 (10 g, 10 mmol) was dissolved in ammonia water (50 mL), and ammonium chloride (5.35 g, 100 mmol) was added. The reaction was carried out at 40 ° C for 72 h, and TLC monitoring (dichloromethane: methanol = 10: 1) was performed. The reaction solution was saturated with sodium chloride, extracted three times with dichloromethane (100 mL × 3), and the organic phases were combined and vortexed until viscous, and then precipitated with cold ether, filtered and dried to obtain a white solid powder (8.7 g, yield 87%).
[0073] 1 H NMR (400MHz, Chloroform-d) δ3.88–3.46 (m, 88H), 3.40 (s, 3H), 2.92 (t, J = 5.2Hz, 2H).
[0074] Synthesis and structural characterization of intermediate compound 5-1:
[0075] The intermediate compound 3-1 (400 mg, 0.2 mmol) was dissolved in N, N-dimethylformamide (10 mL), and then 1,8-diazabicyclo[5.4.0]undec-7-ene, i.e. DBU (200 μl, 2.4 mmol) was added dropwise to the reaction bottle. The solution changed from yellow-orange to red, and reacted at 25°C for 5-30 min, and monitored by TLC (dichloromethane: methanol = 5:1) until the end point. A large amount of cold water was injected into the reaction solution until a large amount of precipitate was precipitated, and then the mixture was placed in a centrifuge tube and centrifuged (6000 rpm, 10 min), and the red precipitate was collected, slurried with petroleum ether, filtered and dried to obtain a red solid powder (116 mg, 54%).
[0076] 1 H NMR (400MHz, DMSO-d6) δ7.93–7.82(m,4H),7.70(s,8H),7.07(d,J=7.5Hz,8H),6.29(s,1H),5.76(s,1H),3.80(d,J=35.9Hz,8H).
[0077] Synthesis and structural characterization of the target product (DAC4A):
[0078] Guanidine hydrochloride (2.66 mg, 0.028 mmol) and di-tert-butyl dicarbonate (44.65 mg, 0.205 mmol) were added to anhydrous ethanol, the reaction temperature was raised to 38°C until dissolved, and the intermediate compound 5-1 was added and reacted at 38°C overnight. TLC monitoring (dichloromethane: methanol = 5: 1) to the end point. The solvent ethanol was removed by vacuum distillation, and the residue was slurried with petroleum ether to obtain a red powder, which was washed with a saturated NaCl solution and dried to obtain the intermediate compound 5-2. The intermediate 5-2 (50 mg, 0.03 mmol) was dissolved in tetrahydrofuran (8 mL), 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate (91 mg, 0.24 mmol) and N,N-diisopropylethylamine (63 μl, 0.36 mmol) were added, activated at 60°C for 20 min, polyethylene glycol monomethyl ether amino (180 mg, 0.18 mmol) was added, and the reaction was carried out at 60°C for 12 h. The solution was transferred into a dialysis bag (MWCO: 1500 Da), dialyzed in high-purity water for 24 h to remove impurities, and then freeze-dried to obtain a red powder. The powder was dissolved in 25 mL of dichloromethane, 5 mL of trifluoroacetic acid was added, and the mixture was reacted at room temperature for 2 h. The solvent was removed by distillation under reduced pressure. The crude product was dissolved in 20 mL of saturated sodium bicarbonate solution, extracted with dichloromethane (50 mL × 2), and the organic phases were combined and the solvent was removed by distillation under reduced pressure to obtain a red powder, i.e., the target product (DAC4A) (63 mg, yield 46%).
[0079] 1H NMR(400MHz,Chloroform-d)δ8.83(s,4H),8.50(s,8H),8.10(d,J=7.5Hz,4H), 7.70(s,8H),7.62(s,4H),3.82(s,8H),3.67(s,352H),3.37(d,J=22.2Hz,12H).
[0080] Example 2
[0081] Determination of the binding constant between azocalixarene (DAC4A) and curcumin
[0082] Test tools: The test uses a quartz cuvette as the sample cell, the excitation wavelength is 365nm, the excitation slit is 5nm, the emission slit is 10nm, and the instrument is a Hitachi fluorescence spectrophotometer (F-2710FL fluorescence).
[0083] The binding constant of azocalixarene (DAC4A) and rhodamine B was determined by direct fluorescence titration. DAC4A and RhB stock solutions were prepared with PBS buffer at pH 7.4 as solvent, and the concentrations of both solutions were 10 μM. During the test, RhB was diluted to 0.5 μM and added to a fluorescence cuvette. The volume of PBS was adjusted to 2 mL (the final concentration of RhB was 0.375 μM), and the initial fluorescence intensity of the RhB solution was measured and recorded. Subsequently, the DAC4A solution was added dropwise to the fluorescence pool at a predetermined volume, keeping the final concentration of RhB unchanged. The changes in fluorescence intensity and the corresponding host concentration were used to determine the binding constant K of DAC4A and RhB. a The data were fitted according to a 1:1 binding stoichiometry. The binding constant of DAC4A and Cur was determined by competitive fluorescence titration. The competitive substance Cur was gradually added to the RhB@DAC4A solution for competitive fluorescence titration. The fluorescence intensity at the emission wavelength of RhB and the Cur concentration were fitted according to the 1:1 competitive binding model. Each titration experiment was performed three times in parallel. K a Take the average of the three test results, and the fluorescence titration spectrum results are as shown in the attached Figure 7 As shown in A and C. The curve fitting was performed using Origin based on the changes in fluorescence intensity and the corresponding host and curcumin concentrations. The results are shown in the attached figure. Figure 7 As shown in B and D, the binding constants K of DAC4A to RhB and Cur a They are (1.01±0.08)×10 7 M -1 and (5.0±0.4)×10 5 M -1 .
[0084] Example 3
[0085] Preparation and characterization of azocalixarene (DAC4A) drug-loaded nanomicelles:
[0086] DAC4A (10 mg, 2 μmol) and curcumin (1.84 mg, 10 μmol) were accurately weighed and placed in a glass bottle, dissolved in 3 mL of chloroform, and the solvent was evaporated under reduced pressure to obtain a uniform thin film; 10 mL of PB buffer solution (pH 7.4, 10 mM) preheated to 37°C was added, and ultrasonication was continued for 5-10 min, and filtered through a 0.45 μm microporous membrane to obtain nanomicelles loaded with curcumin. The particle size was measured by DLS as shown in the attached figure. Fig.13 As shown in A, the average particle size is about 150 nm and the PDI is 11.64%.
[0087] DAC4A (10 mg, 2 μmol) was accurately weighed and placed in a glass bottle, dissolved in 3 mL of chloroform, and the solvent was evaporated under reduced pressure to obtain a uniform thin film; 10 mL of PB buffer solution (pH 7.4, 10 mM) preheated to 37°C was added, and ultrasonication was continued for 5-10 min, and filtered through a 0.45 μm microporous membrane to obtain an empty nano drug delivery system, the particle size of which is as shown in the attached Fig.13 As shown in B, the average particle size is about 200 nm and the PDI is 19.39%.
[0088] By the results Figure 8 It can be seen that compared with the empty nano-drug delivery system, the particle size and polydispersity index of the calixarene nano-micelles decreased significantly after encapsulating curcumin, indicating that the combination of curcumin and the hydrophobic cavity further increased the overall hydrophobic ratio of the material, making the internal hydrophobic area more compact and forming a smaller particle size.
[0089] Fourier infrared spectroscopy characterization of azocalixarene (DAC4A) nanomicelles:
[0090] The chemical structure of the nano drug delivery system was analyzed using an infrared spectrometer equipped with an attenuated total reflectance (ATR) accessory. The free curcumin Cur, the freeze-dried blank and the drug-loaded nano drug delivery system, and the physical mixture of DAC4A and Cur were analyzed at 4000-400 cm -1 Scan within the range, the results are as shown in the attached Fig. 9 As shown, Cur at 3500cm -1 Nearby is the stretching vibration peak of the OH bond on the phenolic hydroxyl group, 1600-1750cm -1 Nearby is the stretching vibration peak of the C=O carbonyl group, 1550cm -1 Nearby is the stretching vibration peak of C=C, 1000-1250cm -1 It is the characteristic absorption peak of -COC- ether bond; DAC4A is at 3250cm -1 Nearby is the NH stretching vibration peak of the primary amine, 2800 cm-1 Nearby is the characteristic absorption peak of CH on the polyethylene glycol chain, 1650cm -1 Nearby is the NH bending vibration absorption peak of primary amine, 1450cm -1 With 1550cm -1 Nearby are the C=O stretching vibration peak and N=N stretching vibration peak, 1250-1350cm -1 It is the CN stretching vibration peak of aromatic amine, 1150cm -1 Nearby is the COC stretching vibration peak on the polyethylene glycol chain.
[0091] Compared with the blank and drug-loaded nano-delivery systems, the non-covalent interactions such as hydrogen bonds between DAC4A and Cur molecules affect the bond force constants between hydrogen atoms and their connected functional groups, resulting in the characteristic absorption peak of curcumin Cur at 1650 cm -1 、1550cm -1 、3500cm -1 It obviously disappeared, proving that the drug was successfully encapsulated.
[0092] Example 4
[0093] Determination of encapsulation efficiency and drug loading of azocalixarene (DAC4A) nanomicelles:
[0094] The reverse dialysis method was used to determine the encapsulation efficiency and drug loading of the nano drug delivery system. The drug-loaded nano micelles were prepared using the method in Implementation 3. 5 mL of the prepared drug-loaded nano micelle suspension was dispersed in 150 mL of 15% ethanol. 5 mL of 15% ethanol was placed in a dialysis bag (MWCO: 1000Da). 1 mL of the dialysate in the dialysis bag was drawn every 2 hours. The absorbance value was measured using an ultraviolet spectrophotometer, and the same volume of medium was added. The measured absorbance value was calculated using the curcumin standard curve to obtain the free drug concentration. Using formula (1-3), the encapsulation efficiency of the drug-loaded nano drug delivery system was 75.23 ± 1.14%, and the drug loading was 11.62 ± 0.8%.
[0095]
[0096] in
[0097] M: total drug mass added (mg);
[0098] m: free drug mass (mg);
[0099] Example 5
[0100] In vitro drug release assay of azocalixarene (DAC4A) nanomicelles:
[0101] The drug-loaded DAC4A nanomicelles were prepared using the nanomicelle preparation method in Example 3. The prepared drug-loaded micelles were taken and transferred to a dialysis bag, respectively placed in a PB buffer solution (pH 7.4, 10 mM) and a PB solution containing 0.2% SDS, and then placed in a 37°C constant temperature shaker. The release medium was taken from the release medium every 1 hour and the same volume of medium was added. The content of curcumin was then determined by a fluorescence spectrophotometer with an excitation wavelength of 425 nm, an excitation slit of 5 nm, and an emission slit of 10 nm. The results are shown in the attached figure. Fig.10 As shown, compared with the PB solution, the release efficiency of the drug-loaded micelles in the PB solution containing 0.2% SDS can reach more than 80% within 10 hours, while the release efficiency of the control group is less than 40% within 24 hours.
[0102] Example 6
[0103] Stability test of azocalixarene (DAC4A) nanomicelles:
[0104] The nanomicelle preparation method in Example 3 was used to prepare empty and drug-loaded DAC4A nanomicelles. The prepared drug-loaded micelles were placed in a 10% FBS PBS solution to simulate the body fluid environment, and then placed in a 37°C constant temperature shaker. Samples were taken on days 1, 2, 3, 4, and 5, respectively, and the particle size changes were detected using DLS. Fig.11 It can be proved that the particle size of the drug-loaded micelles remains basically unchanged, indicating that the prepared nano-drug delivery system has good stability in simulated body fluid circulation.
[0105] Example 7
[0106] In vitro simulated hypoxic cleavage of azocalixarene (DAC4A):
[0107] In the in vitro hypoxic cleavage of DAC4A, sodium dithionite (SDT) was used to simulate azoreductase to achieve the cleavage of azo bonds. The cleavage was characterized by scanning the UV absorption spectrum and detecting the change in the azo bond absorption peak at 365 nm. A DAC4A solution (1 mg / mL) was prepared as a sample solution using 5 mL of PBS at pH 7.4 as a solvent. Sodium dithionite (0.17 g, 1 mmol) was weighed and dissolved in 5 mL of PBS to obtain an SDT solution. Take 1 mL of the sample solution and gradually add the SDT solution to it, keeping the sample concentration unchanged, place it in a 37°C water bath, take samples at 365 nm wavelength every 2 minutes, measure the UV absorbance three times in parallel, and take the average value. The relationship between the average value and time is used to draw a curve. The results are shown in the attached figure. Fig.12 As shown in Figure A, with the continuous addition of SDT solution, the UV absorption spectrum of DAC4A changes significantly, and the absorbance value at 365nm gradually decreases. When the drop amount is 1mL, the absorbance value basically drops to the minimum. Fig.12As shown in B, after adding 1 mL of SDT solution, the azo bond absorption peak quickly dropped to the minimum within 2 minutes, indicating that DAC4A has good anoxic cleavage ability.
[0108] Example 8
[0109] In vitro nitric oxide absorption test of azocalixarene (DAC4A):
[0110] (1) Determination of in vitro nitric oxide absorption by ultraviolet absorption method:
[0111] Saturated NO solution (1.8 mM at 20 °C) was prepared as a stock solution by slowly dropping 2 M H2SO4 into a glass flask containing a saturated NaNO2 aqueous solution to generate NO.
[0112] The principle of this method is that NO will react with o-phenylenediamine structure to generate benzotriazole and hydrolyze. The structural change leads to obvious ultraviolet absorption at around 350nm.
[0113] A stock solution with a DAC4A content of 50 μM was prepared using PBS at pH 7.4 as solvent. 1 mL of the solution was placed in an EP tube, and sodium dithionite (8.75 mg, 0.05 mmol) was added to obtain a sample solution. Another 1 mL of the stock solution was placed in an EP tube without any treatment as a control group. The NO stock solution (1.8 mM) was diluted into a series of 0-180 μM concentration gradient solutions, and 1 mL of the above different concentration gradient solutions was placed in the sample tube and the control tube. After incubation for 30 minutes, the absorption curve of each mixed solution at 200-600 nm was measured using a UV spectrophotometer. The results are shown in the attached figure. Fig.13 As shown in Figure 1, Figure A is the initial UV spectrum of the sample group after SDT treatment. Figure B shows that with the increase of NO concentration, the absorption peak at 350nm increases significantly, while the control group in Figure C has no obvious change. This shows that the material can only show obvious NO absorption effect after SDT fracture.
[0114] (2) Griess method for determination of in vitro nitric oxide absorption:
[0115] The principle of this method is that NO is oxidized to nitrite in the presence of Griess reagent, which promotes the formation of azo dyes. The ultraviolet absorption value of the dye at 540nm is proportional to the amount of NO.
[0116] Use PBS (pH 7.4, 10mM) buffer to prepare DAC4A and SDT stock solutions, with the concentration of both being 10mM. Take several EP tubes, numbered A, B, C, and D, and prepare each group in turn according to the following formula;
[0117] A: 80 μl DAC4A solution (10 mM) + 100 μl SDT solution (10 mM) + 20 μl 37% hydrochloric acid;
[0118] B: 80 μl PBS + 100 μl SDT solution (10 mM) + 20 μl 37% hydrochloric acid;
[0119] C: 80 μl DAC4A solution (10 mM) + 100 μl PBS + 20 μl 37% hydrochloric acid;
[0120] D: 180 μl PBS + 20 μl 37% hydrochloric acid;
[0121] Group A was the experimental group, and groups B, C, and D were the control groups;
[0122] Take 50 μl of the above different solutions in a 96-well plate, set three parallel wells in each group, add 100 μl of NO stock solution and 100 μl of Griess reagent to each well, mix well, incubate at 37°C on a shaker for 10 min, use an ELISA reader in ABS (ultraviolet absorption) mode, select a wavelength of 540 nm, measure the absorbance value, and draw a curve as shown in the attached figure. Fig.14 As shown, after adding hydrochloric acid to eliminate the interference of excess SDT on the results, the absorbance value of group A was significantly reduced compared with groups B, C, and D, indicating that the o-phenylenediamine structure generated under the action of SDT has a more obvious NO absorption effect.
[0123] Example 9
[0124] Cytotoxicity test (MTT) of azocalixarene (DAC4A) nano drug delivery system:
[0125] The MTT method was used to evaluate the toxicity of the DAC4A nano-drug delivery system on macrophages (RAW cells). RAW cells were cultured in RPMI-1640 medium containing 10% fetal bovine serum (FBS) and 1% penicillin / streptomycin at 37°C in a 5% CO2 incubator. First, 100 μl of cell 1640 suspension was plated in a 96-well culture plate, and the cell number was controlled to be 5000 / well. Then, 10 μl of different concentrations of drug-loaded nanomicelles (DAC4A@Cur), blank nanomicelles (blank@DAC4A), and curcumin (Cur) solution were added to each well to make the final concentration of the drug in the cell wells 10, 25, 50, 100, 200, and 500 μg / mL. After incubation for 24 hours, the culture medium was replaced and 10 μl of MTT solution (5 mg / mL) was added to each well, and the plates were placed in an incubator and cultured for another 4 hours. The culture medium containing MTT was then removed, and 150 μl of DMSO was added to each well. After the purple crystals were completely dissolved, the absorbance was measured at 570 nm using a microplate reader.
[0126] As attached Fig.15As shown in the figure, the cytotoxicity results show that as the concentration of DAC4A increases, there is no obvious cell inhibition effect on the empty nanomicelles. Compared with the free drug group, the encapsulation of DAC4A can significantly improve the biological toxicity of the drug. When the concentration is as high as 500μg / mL, the cell survival rate is still maintained at more than 85%. It proves that the azocalixarene has good biocompatibility.
[0127] Example 10
[0128] Intracellular NO uptake assay of azocalixarene DAC4A
[0129] DAF-FM was used to label the NO level in RAW cells, and the intracellular NO absorption characteristics of DAC4A were tested by observing the changes in NO levels. The principle of this method is that DA can pass through the cell membrane, and after entering the cell, it is catalyzed by the esterase in the cell to form DAF-FM that cannot pass through the cell membrane. It has only weak fluorescence itself, but after reacting with NO, it can produce strong fluorescence, with an excitation wavelength of 495nm and an emission wavelength of 515nm.
[0130] 500μl of 1640 suspension of RAW cells was plated in a 24-well culture plate containing a cell crawler, and the number of cells was controlled to be 50,000 / well. After the cells adhered to the wall, LPS (final concentration 1μg / mL) was added to stimulate for 12h to polarize the RAW cells to M1 type. Then 10μl of DAC4A and CAC4A (control group, without NO absorption) were added respectively to make the final drug concentration 500μg / mL. The culture medium was aspirated, washed with 200μl PBS, and 300μl of diluted 5μM DAF-FM DA was added. The volume added was appropriate to fully cover the cells. Incubated at 37℃ for 20min, the culture medium was aspirated, and washed three times with PBS. 200μl 4% paraformaldehyde was fixed at room temperature for 20min, and washed three times with PBS. Finally, 200μl DAPI dye (10μg / mL) was added and incubated with the cells in the dark for 15min, and washed three times with PBS. Grab the slide and make the cell-adherent side contact with the side of the slide with anti-fluorescence quencher, seal the edges with nail polish, and after drying, use a fluorescence microscope to observe and take fluorescence images.
[0131] As attached Fig.16 As shown, after adding DAC4A to RAW cells, the green fluorescence signal was significantly reduced compared with the control group CAC4A and PBS group, indicating that DAC4A can achieve the absorption effect of NO under the overexpression of azoreductase in inflammatory cells.
[0132] Embodiment 11
[0133] Performance evaluation of calixarene DAC4A modified with polyethylene glycol of different molecular weights
[0134] (1) Effects of different molecular weight polyethylene glycol modification on encapsulation, drug loading and particle size
[0135] According to the synthesis method of the target product in implementation 1, aminopolyethylene glycol monomethyl ether (MW = 200), aminopolyethylene glycol monomethyl ether (MW = 550), and aminopolyethylene glycol monomethyl ether (MW = 1000) were selected to modify the calixarene to obtain products PEG4-DAC4A, PEG12-DAC4A, and PEG22-DAC4A, and the control group PEG22-CAC4A was added at the same time. The drug-loaded nanomicelles were prepared by the thin film dispersion method in Example 3, and the particle size and PDI were characterized; the encapsulation efficiency (DLE) and drug loading (DLC) were determined by the reverse dialysis method in Example 4, and the results are shown in Table 1:
[0136] Table 1. Effects of different molecular weight PEG modification on DAC4A encapsulation efficiency, drug loading and particle size
[0137]
[0138] As can be seen from Table 1, with the increase of molecular weight, the micelle particle size gradually increases and the PDI becomes narrower, thanks to the increase in molecular weight resulting in an increase in the proportion of the hydrophilic part and the thickening of the nanomicelle hydration layer; and with the growth of the molecular chain, a larger particle size tends to be formed on a spatial scale. At the same time, it is observed that the encapsulation efficiency and drug loading are gradually increasing, thanks to the large hydrophobic cavity that can accommodate more hydrophobic drugs.
[0139] (2) Effects of different molecular weight polyethylene glycol modifications on hypoxic response
[0140] Accurately weigh sodium dithionite (174 mg, 1 mmol) and dissolve it in 2 ml PBS to obtain a 500 mM SDT solution. Accurately weigh PEG4-DAC4A (1.8 mg), PEG12-DAC4A (3.2 mg), and PEG22-DAC4A (5 mg) and dissolve them in 1 ml PBS to obtain a sample solution with a concentration of 1 mM. Dilute the SDT solution to different concentration gradients and add them to the above sample solutions in sequence. Use ultraviolet spectrophotometry to measure the absorbance value at 365 nm, and draw a concentration-absorbance curve. The results are shown in the attached figure. Fig.17 shown.
[0141] Depend on Fig.17It can be seen that compared with PEG4-DAC4A, the other two polyethylene glycol modifications have no obvious effect on the hypoxic response, and when the SDT concentration reaches 80mM, the azo bond can be clearly broken, which proves that PEG12-DAC4A and PEG22-DAC4A have good hypoxic responsiveness, while PEG4-DAC4A has insufficient hypoxic responsiveness, which is related to the low hydrophilic ratio in the molecule, resulting in poor dispersibility.
[0142] (3) Effects of different molecular weight polyethylene glycol modification on NO absorption in vitro
[0143] The sample solutions prepared in (2) were added with 100 mM SDT solution to simulate hypoxia in vivo. The in vitro NO absorption was then measured using the Griess method in Example 8. The results are shown in the attached figure. Fig.18 As shown in the figure, with the extension of the action time, compared with the control group PBS and PEG22-CAC4A, the residual NO in the sample group showed a decreasing trend to varying degrees, and there was a significant decrease in PEG12 and PEG22 modification, with the NO absorption rate reaching about 75% in 25 minutes, while the NO absorption rate after PEG4 modification was less than 40%. It proves that there is a significant positive correlation between the degree of hypoxia response and NO absorption, and there is no significant difference in NO absorption between PEG12 and PEG22 modification, and PEG4 modification will make the NO absorption effect worse, because the lack of hydrophilic segments in the molecule leads to poor dispersibility and solubility, and it cannot fully react with NO molecules.
[0144] (4) Effects of different molecular weight polyethylene glycol modifications on DPPH radical scavenging
[0145] The DPPH free radical scavenging rate is an important indicator of the level of active oxygen scavenging and plays a key role in the screening of anti-inflammatory active molecules. Determining the effect of different molecular weight modifications on the DPPH free radical scavenging of materials can further optimize the materials.
[0146] The specific operation is as follows: prepare 0.2mmol DPPH solution and sample solution (PEG4-DAC4A, PEG12-DAC4A, PEG22-DAC4A), and the sample solution is treated with SDT. Prepare a positive control group, 0.2mmol VC solution; and a negative control PBS group. In a 96-well plate, add 50μL of DPPH solution and 150μL of sample solution respectively, and set up 3 replicate wells. After mixing, use an enzyme reader to measure the absorbance value at a wavelength of 517nm. The absorbance value is Aj, and the control group is a solution with only DPPH added. The absorbance value is Ac, and the DPPH free radical scavenging rate is calculated as follows:
[0147]
[0148] K——free radical scavenging rate
[0149] A i ——Absorbance value measured immediately
[0150] A j ——Absorbance value after a period of reaction
[0151] A c ——Absorbance value of the control group
[0152] The results are attached Fig.19 As shown in the figure, compared with the VC group, PEG12-DAC4A has the best DPPH clearance rate, reaching about 75% in 20 minutes, and PEG22-DAC4A is about 60%. However, PEG4-DAC4A is only less than 50%. The results show that different PEG modifications have a significant effect on DPPH. Good DPPH clearance requires sufficient hydrophilic segment modification to make the molecule more dispersible in the solution and easy to clear. Insufficient hydrophilic segment modification will significantly reduce the DPPH clearance ability.
[0153] Therefore, the PEGylated calixarene compound of the present invention can achieve drug release and nitric oxide absorption in a hypoxic environment, and as a calixarene nano drug delivery system, it has important application value in the synergistic treatment of hypoxia-related inflammation by drug loading and nitric oxide absorption.
Claims
1. A polyethylene glycol calixarene compound, characterized in that: The compound structure is shown in Formula I: Here, n is an integer of 4 to 8, and m is an integer of 2 to 44.
2. A method for preparing the PEGylated calixarene compound according to claim 1, characterized in that: The following steps are involved: (1) Using 4-tert-butylcalixarene and phenol as raw materials, a calixarene is obtained by reverse Friedel-Crafts alkylation in a toluene solution containing aluminum chloride, thereby forming a macrocyclic molecular skeleton 1-1; (2) Using 3,4-diaminobenzoic acid and 9-fluorenylmethyl-N-succinimidyl carbonate as raw materials, a single protection of the meta-amino group is achieved through a nucleophilic reaction to form intermediate 2-1; (3) The macrocyclic molecular skeleton 1-1 and the intermediate 2-1 are subjected to diazotization reaction to obtain the intermediate 3-1; (4) Using polyethylene glycol monomethyl ether and p-toluenesulfonyl chloride as raw materials, intermediate 4-1 was synthesized, and then stirred in aqueous ammonia to obtain intermediate 4-2; (5) The intermediate 3-1 is deprotected by 1,8-diazabicyclo[5.4.0]undec-7-ene, i.e., DBU, and the meta-amino group is protected by Boc, and then connected with the intermediate 4-2 by amidation reaction, and the Boc protection is removed to obtain a pegylated calixarene compound.
3. The preparation method according to claim 2, characterized in that: Its synthetic route, step (1) is: Step (2) is: Step (3) is: Step (4) is: Step (5) is:
4. A PEGylated calixarene nanomicelle, characterized in that: The nano micelle is prepared from the polyethylene glycol calixarene compound described in claim 1, with the hydrophilic chain end facing outward and exposed in the water phase, and the hydrophobic benzene ring skeleton facing inward to form a core, forming a stable spherical structure micelle with multiple cavities on the surface.
5. A method for preparing the nanomicelles according to claim 4, characterized in that: The method comprises the following steps: weighing polyethylene glycol calixarene compounds and drugs, fully dissolving them in organic phase, removing the solvent by reduced pressure evaporation to obtain a uniform film; adding preheated water phase, continuing ultrasonication, filtering with a filter membrane to obtain nano micelles.
6. The preparation method according to claim 5, characterized in that: The organic phase is chloroform, the aqueous phase is PB buffer solution, and the ratio of organic phase to aqueous phase is 1:2-5 (v:v).
7. The preparation method according to claim 5, characterized in that: The ultrasonic time is 5-20min, and the solution is filtered through a 0.45μm filter membrane.
8. Use of the PEGylated calixarene compound according to claim 1 or the PEGylated calixarene nanomicelles according to claim 8 in regulating nitric oxide absorption under hypoxic conditions.
9. Use of the PEGylated calixarene compound according to claim 1 or the PEGylated calixarene nanomicelles according to claim 8 in the preparation of anti-inflammatory drugs.
10. The use according to claim 9, characterized in that: The application is to prepare an anti-inflammatory drug by synergistically using the PEGylated calixarene compound of claim 1 or the PEGylated calixarene nanomicelles of claim 8 and curcumin.
Citation Information
Patent Citations
Preparation method for polyglycol modified amphipathic calixarene
CN101367934A
Calix [4] arene derivative as well as preparation and application thereof
CN112126056A
Preparation method and application of calixarene modified albumin capable of simultaneously delivering multiple drugs and accurately regulating and controlling drug proportions
CN114652849A
Preparation method and application of supramolecular nano tracer for tracing drug release in real time and realizing efficient combination therapy
CN118772012A
Calixarene-based targeted drug delivery system as well as preparation method and application thereof
CN118806915A